Seroprevelance study of Toxoplasma gondii in horses and camels animal in Wasit province: Shoob Naser Asal and Ibrahim A. Al Zubaidy - Asal, Shoob Naser (The Iraqi Journal of Veterinary Medicine, 2022)
The aim of this study was to investigate the seroprevelance of Toxoplasma gondii in camels and horses in Wasit province and to determine the seroprevalence of Toxoplasmosis in certain animals farm in Wasit province, also this study included the extent of the disease in camels and horses within two months starting from the January until February of 2015. A total of 184 samples were collected of them 92 horses and 92 camels. The results showed that the incidence of Toxoplasma gondii in horses was 18.4%, in camels 20.6% and the infection percentage of females were more than that males in both horses and camels 21.1 and 20.2%, respectively. Also the present results revealed that younger animals infections were more than in older animals; as well, the percentage of infection in January was more than the incidence in February in each of the horses and camels.